2023
DOI: 10.5455/ovj.2023.v13.i9.9
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplant for treatment of diarrhea in adult hospitalized horses – 111 cases (2013 – 2018)

Camilla Quattrini,
Rana Bozorgmanesh,
Patricia Egli
et al.

Abstract: Background: Fecal microbiota transplant (FMT) is increasingly administered as part of the treatment of colitis in horses, yet there are little data as to effectiveness. Aim: Retrospective evaluation of the effects of FMT on discharge status, fecal consistency, length of hospitalization and improvement in clinical signs in horses hospitalized for diarrhea. Methods: Retrospective case-control study. Medical records of adult horses (>1 year old) that received at least one transfaunation treatment (2013-201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, it is worth noting that this particular study utilized a relatively small amount of stool (500 g) for the transplantation, which may not have been sufficient to induce significant changes in the gastrointestinal tract of the horse. Additionally, a study involving 111 horses reported no effectiveness of FMT in their cohort ( 22 ). However, it is important to acknowledge that in this study, the authors failed to exclude horses treated with antimicrobials from the statistical analysis when evaluating the efficacy of FMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth noting that this particular study utilized a relatively small amount of stool (500 g) for the transplantation, which may not have been sufficient to induce significant changes in the gastrointestinal tract of the horse. Additionally, a study involving 111 horses reported no effectiveness of FMT in their cohort ( 22 ). However, it is important to acknowledge that in this study, the authors failed to exclude horses treated with antimicrobials from the statistical analysis when evaluating the efficacy of FMT.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that these studies were not case-controlled and involved horses from various locations with differing health statuses serving as controls. Conversely, other studies have demonstrated no discernible impact of FMT on gastrointestinal issues in horses (19)(20)(21)(22). Consequently, it is crucial to approach these findings with caution and acknowledge the necessity for further research to enhance the efficacy of FMT in equine care.…”
Section: Introductionmentioning
confidence: 97%
“…A decrease in the symptom’s severity was reported, but horses were evaluated by their owners non-blinded, which might have introduced bias to their evaluation. Quattrini et al performed a retrospective study using records from 111 cases of colitis from two equine hospitals [ 177 ]. Non-treated horses had significantly shorter hospitalization times than the group receiving FMT, and there were no statistical differences in time to normalize fecal consistency, clinical parameters, or mortality.…”
Section: Techniques Of Microbiota Manipulationmentioning
confidence: 99%